C1q/TNF-Related Protein5 (CTRP5) as a Biomarker to Predict Metabolic Syndrome and Each of Its Components - Feiyu Jiang; Min Yang; Xili Zhao; Rui Liu; Gangyi Yang; Dongfang Liu; Hua Liu; Hongting Zheng; Zhiming Zhu; Ling Li (International Journal of Endocrinology)
Objective. C1q/TNF-related protein5 (CTRP5) is a member of the C1q/tumor necrosis factor α- (TNF-α-) related protein family and has been reported to be associated with the regulation of glucose and lipid metabolism. However, the clinical association between CTRP5 and metabolic syndrome (MetS) has not been reported. The aim of the current study is to investigate the association between CTRP5 and MetS by a cross-sectional study. Methods. We performed a cross-sectional study in a Chinese population including 89 controls and 88 MetS individuals. Serum CTRP5 concentrations were determined by ELISA. The relationship between circulating CTRP5 and MetS and insulin resistance (IR) was assessed by Spearman’s correlation and multiple stepwise regression analysis. Results. Circulating CTRP5 concentrations were markedly decreased in MetS individuals relative to normal adults. Overweight/obese individuals (BMI ≥ 25 kg/m2) showed a lower serum CTRP5 level than lean subjects (BMI < 25 kg/m2) in the study population (124.1 (99.12–147.37) vs. 103.9 (79.15–124.25) μg/L; P<0.01). Circulating CTRP5 was found to be correlated negatively with BMI, FAT%, FBG, WHR, SBP, HbA1c, TG, 2-hour blood glucose after glucose overload (2-hOGTT), FIns, and HOMA-IR and positively with HDL-C (P<0.05 or P<0.01). Binary logistic regression revealed that serum CTRP5 levels were associated with MetS. In addition, serum CTRP5 levels gradually decreased with the increase in MetS components. Conclusions. Circulating CTRP5 is relative to the elevated risk of MetS in humans and may be in part through the effect of insulin resistance. This trial is registered with ChiCTR-OCS-13003185.